An Evaluation of Factors Considered while Selecting Mutual Funds: A Case of Brokers in Punjab - Sahi, Anu; Pahuja, Dr. Anurag; Dogra, Dr. Balram (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
The past years have been a defining period for the mutual fund industry, as lack of incentivisation has made it increasingly burdensome for the distributor to reach out to the retail investor. Rather, role of distribution channel is phenomenal in delivery of product or service. Majority of the investors relies on financial advisors for choosing mutual funds. Hence, it is imperative to unveil the factors considered while selecting mutual funds and attributes affecting success of mutual funds. It is a maiden effort in this regard, since no such empirical study as per best of our knowledge has been conducted in the state of Punjab till date.